Organ Donation and Transplantation - Mihaylov, Vassil (IntechOpen, 2021)
This book brings together knowledge from different fields of science and presents advances in organ transplantation and donation. It uses a multidisciplinary approach to examine the complex issues of the transplant process. Written by experts in the field, this volume is suitable for medical specialists and medical students alike.